A novel hay-derived biochar for removal of tetracyclines in water. (February 2019) - Jang, Hyun Min; Kan, Eunsung
Highlights: Alfalfa and bermudagrass-derived biochars were used for removal of tetracycline. Based on the physicochemical properties, adsorption mechanisms were explained. The alfalfa-derived biochar has exhibited outstanding TC adsorption capacity. Adsorption capacity of alfalfa-derived biochar was compared to commercial ACs. Alkaline regeneration led to effective adsorption–desorption for multiple cycles. Abstract: The biochars derived from alfalfa (AF) and bermudagrass (BG), the abundant grass hays to cows, were prepared, characterized and used for removal of tetracycline (TC) in water. The alfalfa-derived biochar (AF-BC) has exhibited outstanding TC adsorption capacity (372 mg/g), which was about 8-fold higher than that of bermudagrass-derived biochar (BG-BC). In addition, the TC adsorption capacity of AF-BC was comparable with those of the commercial activated carbons under the same conditions. The surface structure, chemistry and high ash contents of AF-BC suggested the hydrogen bonding, electrostatic interactions and surface complexation between AF-BC and TC. Furthermore, hydroxyapatite (HAP; Ca5 (PO4 )3 OH) and calcite (CaCO3 ) on the surface of AF-BC may also contribute to adsorption of TC via surface complexation, hydrogen bonding and electrostatic interactions. The alkaline desorption-driven regeneration of TC-spent AF-BC led to effective adsorption–desorption for multiple cycles, which indicated AF-BC could be a cost-effective adsorbent for TC in water and wastewater.